Effect of PCDH7 on LPS-induced renal tubular epithelial cell pyroptosis - Wang Yanling, Tan Fang, You Yiying, Yu Xiaofang, Huang Fei (Xin yixue, 2022)
Objective To investigate whether protocadherin 7 （PCDH7） participates in the progress of renal tubular epithelial cell pyroptosis induced by lipopolysaccharide （LPS）. Methods HK-2 cell was stimulated by 2 μg/mL LPS to construct renal tubular epithelial cell injury model. The changes in the expression levels of PCDH7, NLRP3, caspase-1, and IL-1β in cells were detected by RT-PCR and western blot. MTT assay was used to detect cell viability. TUNEL assay was employed to determine pyroptosis rate. ELISA was adopted to detect the secretion of TNF-α and IL-6 in cells. The content of lactate dehydrogenase （LDH） in culture medium was detected by automatic biochemical analyzer. Results Compared with the control group, cell viability was decreased, while pyroptosis rate was increased. The expression levels of TNF-α and IL-6 were up-regulated. The expression level of LDH, a biomarker of cell damage, was significantly elevated. The expression levels of PCDH7 and mRNA were significantly down-regulated. The expression levels of NLRP3, caspase-1, IL-1β and mRNA were significantly up-regulated in the LPS group （all P < 0.05）. Conclusion LPS can induce renal tubular epithelial cell pyroptosis by down-regulating the expression of PCDH7.